Chylous Ascites: Evaluation and Management. (3rd February 2014) - Al-Busafi, Said A.; Ghali, Peter; Deschênes, Marc; Wong, Philip
Abstract : Chylous ascites refers to the accumulation of lipid-rich lymph in the peritoneal cavity due to disruption of the lymphatic system secondary to traumatic injury or obstruction. Worldwide, abdominal malignancy, cirrhosis, and tuberculosis are the commonest causes of CA in adults, the latter being most prevalent in developing countries, whereas congenital abnormalities of the lymphatic system and trauma are commonest in children. The presence of a milky, creamy appearing ascitic fluid with triglyceride content above 200 mg/dL is diagnostic, and, in the majority of cases, unless there is a strong suspicion of malignancy, further investigations are not required in patients with cirrhosis. If an underlying cause is identified, targeted therapy is possible, but most cases will be treated conservatively, with dietary support including high-protein and low-fat diets supplemented with medium-chain triglycerides, therapeutic paracentesis, total parenteral nutrition, and somatostatins. Rarely, resistant cases have been treated by transjugular intrahepatic portosystemic shunt, surgical exploration, or peritoneovenous shunt.